Flying Through Uncertainty - T. E. Berger; M. J. Holzinger; E. K. Sutton; J. P. Thayer (Space Weather)
Abstract Space weather is the main source of uncertainty in the position of all objects in low Earth orbit (LEO) below about 1,000 km. The main impact is strong variation in the neutral density of the thermosphere as it responds to radiative inputs from the Sun in the extreme ultraviolet wavelength range, energetic particle precipitation in the high‐latitude auroral zones, and global‐scale electrical currents generated during geomagnetic storms. Waves and instabilities from the lower atmosphere can also influence thermospheric density in complex ways. The variation in neutral density leads to variable drag forces on satellites flying through the thermosphere, which in turn causes orbital track changes. We currently lack the ability to accurately model and predict the neutral density changes in the thermosphere in response to space weather inputs. Operational empirical models of thermospheric density are inaccurate during space weather events, and mandate that LEO orbital tracks carry large “error ellipsoids” around all objects to account for positional uncertainty. This leads to many more “conjunction” warnings than necessary as large error ellipsoids are frequently calculated to intersect in orbit. As the LEO domain becomes more crowded with the advent of commercial “megaconstellations” we face a growing challenge to reduce orbital uncertainties by developing whole atmosphere models to enable timely and accurate forecasts of thermospheric conditions. We recommend that researchers, forecasters, and policy makers coordinate to ensure that space weather research and forecasting is tightly integrated into upcoming changes to the operational Space Traffic Management system.